Nîmes dans l’œuvre narrative de Georges Gros - Claire Torreilles (Revue des Langues Romanes)
In the poetic geography of Georges Gros, Nîmes occupies a central place. From the labyrinth of the streets of the Placette district, where childhood seeks its bearings, to the paths of the garrigue whose names evoke a world now lost, to the novelistic anchoring in the new districts of the ZUP, lights, smells, dreams and faces emerge vividly from memory or history.